The Hamilton phenomenon - Northrop, Chloe (Vernon Press, 2022)
The Hamilton Phenomenon' brings together a diverse group of scholars including university professors, librarians, educators at community colleges, Ph.D. candidates, and independent scholars, in an exploration of the celebrated Broadway hit. When Lin-Manuel Miranda's musical sensation erupted onto Broadway in 2015, scholars were underprepared for the impact the theatrical experience would have.